PENERAPAN METODE TRADITION-HISTORICAL DALAM MUṢANNAF ‘ABD AL-RAZZĀQ AL-ṢAN‘ĀNĪ DAN IMPLIKASINYA TERHADAP PERSOALAN DATING HADIS DAN PERKEMBANGAN FIKIH MEKKAH - Ali Masrur (Jurnal Theologia, 2013)
Abstract: This research studies in the application of the method of tradition-historical in the Muṣannaf of ‘Abd al-Razzāq al-Ṣan‘ānī and its implication to the problem of dating ḥadīṡ and the development of Meccan fiqh. By using the method of tradition-historical, Motzki proved that Muṣannaf of ‘Abd al-Razzāq al-Ṣan‘ānī (d. 221 H.) can be trusted as a source of authentic aḥādīṡ of the first century of hijrah. The implications of applicating this method of tradition-historical to the development of the Meccan fiqh are: first, it is proved that in the first century of hijrah, the people of Mecca had referred to the Quran and the prophetic rules as a source of Islamic Law. Second, the development of ḥadīṡ from Successor’s ḥadīṡ to be Companion’s ḥadīṡ and then to be Prophetic ḥadīṡ is a construct that is not tenable based on this research. Third, regional schools of legal and religious schoolarship can already be discerned in the last three dacade of the first/sevent century. Therefore, the statement of Schacht that Islamic law did not existed yet in the first century of hijrah must be revised. Fourth, the development from a jurisprudence primarily articulated through ra’y to one based on Tradition was a process that began already at the end of the first/seventh century within the schools and which–at least in the Hijaz–is to be understood as the result of the collection, not merely of forging of traditions. The Collection and transmission of texts was carried out not only with the intention of supporting particular opinions of the schools, but also independently of this. Abstrak: Riset ini mengkaji aplikasi metode tradition-historical dalam Muṣannaf karya ‘Abd al-Razzāq al-Ṣan‘ānī dan implikasinya terhadap persoalan penanggalan (dating) hadis dan perkembangan fikih Mekkah. Dengan menggunakan metode tradition-historical, Motzki membuktikan bahwa Muṣannaf karya ‘Abd al-Razzāq al-Ṣan‘ānī (w. 221 H) bisa dipercaya sebagai sumber hadis-hadis otentik dari abad I H. Implikasi-implikasi dari menerapkan metode tradition-historical ke perkembangan fikih Mekkah adalah: pertama, terbukti bahwa pada abad I H, penduduk Mekkah yang merujuk kepada al-Quran dan peraturan-peraturan kenabian sebagai sebuah sumber Hukum Islam. Kedua, perkembangan hadis dari hadis Pewaris menjadi hadis Sahabat serta kemudian hadis Nabi adalah sebuah kontruk yang tidak dapat dipercaya berdasarkan riseti ini. Ketiga, mazhab-mazhab hukum regional dan ilmu pengetahuan agama sudah sangat dikenal pada akhir tiga dekade pada abad I H/VII M. Oleh karena itu, pernyataan Schach bahwa hukum Islam tidak eksis sampai abad I H harus direvisi. Keempat, perkembangan dari yurisprudensi khususnya artikulasi melalui ra’y hingga berdasarkan pada Hadis (Tradition) adalah sebuah proses yang sudah dimulai pada akhir abad I H/VII M dalam mazhab-mazhab itu dan yang—setidak-tidaknya di Hijaz—dipahami sebagai hasil dari koleksi, bukan semata-mata membatalkan hadis-hadis. Koleksi dan transmisi teks-teks yang dibawa tidak hanya dengan maksud mendukung pendapat-pendapat tertentu dari mazhab-mazhab, tetapi juga bebas darinya. Kata-kata Kunci: Dating hadits, metode tradition-historical, Muṣannaf ‘Abd al-Razzāq, fikih Mekkah.